Acute toxicity of insecticidal chlorfenapyr-containing bait for mice - M. A. Levchenko (Российский паразитологический журнал, 2019)
Objective of research. The aim of this study was to estimate of acute oral toxicity for white mice and determine the hazard class of chlorfenapyr-containing baits for mammals. Materials and methods. The material of study was the insecticidal chlorfenapyr-containing bait containing the active ingredient chlorfenapyr. Experiments were carried out on laboratory animals (white mice of both gender), that after a quarantine for seven days and 24 hours of starvation were given the preparation at the dose 50-1100 mg per kg of body mass. Animals of the control group received a standard feed in the same amount. We observed animals of control and experimental groups for 10 days. According to the results of the experiment, we calculated the lethal doses (LD16, LD50, LD84)using the probit analysis As the half-lethal dose of the bait is in the range of 151-5000 mg/kg, it was referred according to gOsT 12.1.007-76 to the 3rd hazard class (moderate dangerous substances). Results and discussion. The use of the bait at the dose of 50 mg per 1 kg of body mass did not cause any toxic effects. When the dose was increased up to 100 mg per kg of body mass or more, we registered the signs of intoxication in the first 2-4 hours. We observed lethargy, muscular fibrillation, salivation. With the next 10 days no death was registered; the status of animal returned to the normal 24-48 hours after beginning of experiment. The lethal dose (LD) that led to the death of experimental animals was 1100 mg per kg of body mass. Calculated effective doses of the bait were as follows: LD16 186,0 (84,7+408,6); LD50 620,3 (355,6+1082,2), and LD84 2069,0 (941,9+4545,1) mg per kg of body mass. According to our results of acute toxicity parameters for white mice, insecticidal chlorfenapyr-containing bait belongs to the third hazard class (moderately hazardous substances).